2015
DOI: 10.18011/bioeng2015v9n2p151-161
|View full text |Cite
|
Sign up to set email alerts
|

Alteração Das Propriedades Físico-Químicas Na Aplicação Contendo Adjuvantes

Abstract: RESUMOEste trabalho teve como objetivo avaliar as alterações produzidas por doze adjuvantes em algumas propriedades físico-químicas das caldas de aplicação, sobre a área de molhamento de folhas de soja e sobre a alteração no tamanho de gotas. As avaliações foram realizadas sob condições ambientais controladas em laboratório. Foram utilizadas duas pontas de modelo leque na avaliação da variação do tamanho das gotas: jato plano SF; e com pré-câmara TT. A análise da variação do espalhamento da gota sobre a superf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 12 publications
0
9
1
3
Order By: Relevance
“…The figures confirm the statements of AGUIAR JÚNIOR et al (2011), BUENO et al (2013), CUNHA et al (2010, SILVA-MATTE et al (2014) and XU et al (2010). They are contrary to the findings of BAIO et al (2015), however, which highlighted significant differences in surface tension of adjuvants Aureo (Bayer © ) and TA35 (Inquima © ); with lower values for Aureo at the same dose, and similar to TA35 adjuvant , at a ten times higher dose. The incidence and severity of foliar diseases in wheat were affected by fungicide application.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The figures confirm the statements of AGUIAR JÚNIOR et al (2011), BUENO et al (2013), CUNHA et al (2010, SILVA-MATTE et al (2014) and XU et al (2010). They are contrary to the findings of BAIO et al (2015), however, which highlighted significant differences in surface tension of adjuvants Aureo (Bayer © ) and TA35 (Inquima © ); with lower values for Aureo at the same dose, and similar to TA35 adjuvant , at a ten times higher dose. The incidence and severity of foliar diseases in wheat were affected by fungicide application.…”
Section: Resultscontrasting
confidence: 99%
“…When evaluating aqueous solutions with adjuvants for agricultural use at 25 °C, CUNHA et al (2010) concluded that the same adjuvant kept the spray stable, altered its pH, and reduced water surface tension from 71 to 33 mN m -1 . When checking the water physicochemical properties with and without adjuvants, BAIO et al (2015) emphasize that water surface tension was reduced The aim of this study was to verify if the association of adjuvant to fungicide significantly alters the spray physicochemical characteristics and potentiates the chemical control of foliar diseases to the extent that it may affect yield components in wheat and soybean crops.…”
Section: Introductionmentioning
confidence: 99%
“…Cunha et al (2017) evaluated the physicochemical properties of spray mixtures and found that there was a strong interaction effect between adjuvants and pesticides, supporting the results in this study. Baio et al (2015) and Sasaki et al (2015) observed that adjuvants affected surface tension and spray viscosity, respectively. Surface tension ranged from 20.03 to 72.60 mN m -1 and solution viscosity decreased up to 0.04%, which corroborates the present study.…”
Section: Resultsmentioning
confidence: 99%
“…The fungicide mixture alone increased the reduction in droplet diameter from 4.38% to 9.04%. Several studies have already evaluated the evaporation time of droplets on surfaces (Baio et al, 2015;Xu et al, 2010;Yu et al, 2009). This may help understand the evaporation process after droplets reach the target area since surface contact changes droplet shape and evaporation time (Erbil, 2015;Santiago, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of surfactants and adjuvants in the formulated product Roundup Ultra ® may cause changes in the physicochemical characteristics of the water present in the soil solution, such as electrical conductivity, surface tension and pH (DA CUNHA;ALVES, 2009;BAIO et al 2015). The reduction of pH may favour the sorption of sulfentrazone in the soil, since it has a weak acid behaviour.…”
Section: Red-yellow Latosolmentioning
confidence: 99%